Delisting of Liver Transplant Candidates with Chronic HCV Infection after Viral Erradication: Outcome 2 Years after Delisting. A European Study. (July 2018) - Vinaixa, Carmen; Belli, Luca Saverio; Berenguer, Marina; Cortesi, Pablo; Strazzabosco, Mario; Faccheti, Rita; Rockenschaub, Susanne-Rasoul; Martini, Silvia; Morelli, Cristina; Donato, Francesca; Volpes, Ricardo; Pasulo, Luisa; et al.
Abstract : European Liver and Intestine Transplant Association (ELITA). Background and Aims: We showed in a previous ELITA study that second generation Direct Acting Antivirals (DAAs) can lead to a significant clinical improvement of patients listed for liver transplantation (LT) due to decompensated cirrhosis and that 1 patient out of 4 could be removed from the waiting list ("delisted"). The objective of this study is to describe the clinical outcomes 2 years after delisting with particular attention to the risks of death, development of HCC and further re-deterioration. Methods: Between February 2014 and June 2015, 142 HCV positive-patients listed for decompensated cirrhosis without hepatocellular carcinoma (HCC) were treated with DAA. Delisted patients were followed up until November 2017 regularly with liver function tests and abdominal ultrasounds. Results: Forty-two patients (29, 6%) were delisted due to clinical improvement after a median follow up of 52 months from start of therapy. Median Child-Pugh and MELD scores at start of DAA therapy were 9 and 14, respectively. The median median follow up from delisting is now 105 weeks (74-148). One patient died (2.4%) 22 months after delisting due to a rapidly progressing HCC; two patients developed a single nodule of HCC and were re-listed; two other patients re-decompensated and were also relisted. The median Child-Pugh and MELD score of the 37 "still delisted" patients is 5.5 and 9 respectively. Conclusions: After a median follow up of 105 weeks (26 months) from delisting, the outcome of delisted patients is favorable. Longer follow up is needed to confirm these positive outcomes.